Methanimine in cool cosmic objects using accurate collisional rate coefficients - Chandra, S.; Sharma, M. K.
Accurate collisional rate coefficients for collisional transitions between 15 rotational levels of methanimine, colliding with p-H2 molecule, are available. Methanimine is a planar, asymmetric top molecule having electric dipole moment with components μ=1.3396 Debye and μ=1.4461 Debye, and thus, producing both the a and b type spectral lines of nearly equal intensities. Therefore, all the rotational levels need to be considered together. Between 15 rotational levels, 105 collisional transitions are considered in an investigation by others. We have discussed that each level is not connected with all others through the collisions, and therefore, there should be 77 instead of 105 collisional transitions between 15 levels of methanimine. With availability of accurate collisional rate coefficients, it is worth to perform the Sobolev analysis of methanimine. We have found six weak MASER transitions, 110-111, 211-212, 312-313, 41.3-41.4, 303-212 and 40.4-31.3, and one transition 111-202, showing anomalous absorption. These seven lines may play important role for the methanimine.
Keywords: Radiative transfer